Characteristics of mechanical CPR-related injuries: A case series. (February 2020) - Milling, Louise; Mikkelsen, Søren; Astrup, Birgitte Schmidt
Abstract: Introduction: Chest compression is regarded as a vital component of CPR and should be initiated immediately upon recognition of cardiac arrest in order to preserve circulation and thereby maintaining vital functions. Mechanical devices for CPR are still more common in the pre- and in-hospital treatment of cardiac arrest. Injuries due to treatment with these are known to occur. The aim of this case series was to identify and characterize the injury pattern in patients who had received mechanical CPR with focus on the visceral injuries. Method: From 2016 to 2018, we prospectively included all patients who had received out-of-hospital mech-CPR with a LUCAS device in the Region of Southern Denmark (RSD) who were subsequently autopsied. Both hospital and forensic autopsies were included. We excluded cases with age less than 18, trauma immediately preceding the cardiac arrest, or known pregnancy. Results: A total number of 50 cases were included in this study. Overall, 38 (76%) had injuries. In the remaining 12 cases (24%) we found neither skeletal or visceral injuries nor any bruising of the chest. 11 (22%) had visceral injuries. Four patients suffered abdominal injuries. The remaining patients had thoracic injuries only. In five cases, the pathologist considered the injuries life-threatening had the patients otherwise survived. These five cases were less than 55 years old and had no known or observed conditions which could explain the extend of injury. Conclusion: We found five iatrogenic injuries which in itself could have been fatal had the patients survived the incident. It is of great importance for the forensic pathologists to be aware of the possible types of injuries and their severity caused by compressions when dealing with patients treated with mechanical CPR as they are both diverse and can be extensive. Highlights: Mechanical cardiopulmonary resuscitation may cause severe injuries. Life-threatening injuries caused by mechanical cardiopulmonary resuscitation occur. It is important for the forensic pathologist to recognize CPR related injuries.